2022
DOI: 10.3390/en15020420
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analysis of the Impeller Backside Cavity in a Centrifugal Compressor for CAES

Abstract: Relying on a closed test rig of a high-power intercooling centrifugal compressor for compressed air energy storage (CAES), this study measured the static pressure and static temperature at different radii on the static wall of the impeller backside cavity (IBC) under variable rotating speeds. Simultaneously, the coupled computations of all mainstream domains with IBC or not were used for comparative analysis of the aerodynamic performances of the compressor and the internal flow field in IBC. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…These technologies store energy until it is needed [109]. Various energy systems are available such as supercapacitors [110,111], batteries [112,113], flywheel [114,115], compressed air [116,117], thermal energy storage [118,119], pumped hydro [120], and others. Table 6 shows a comparison between the different storage systems, and Table 7 shows the largest energy storage systems installed around the globe.…”
Section: Energy Managementmentioning
confidence: 99%
“…These technologies store energy until it is needed [109]. Various energy systems are available such as supercapacitors [110,111], batteries [112,113], flywheel [114,115], compressed air [116,117], thermal energy storage [118,119], pumped hydro [120], and others. Table 6 shows a comparison between the different storage systems, and Table 7 shows the largest energy storage systems installed around the globe.…”
Section: Energy Managementmentioning
confidence: 99%
“…After one year, he investigated the effect of rotational speed and variable angles on the aerodynamic performance of centrifugal compressors [15]. Then, he investigated the static temperature and static pressure of the impeller backside cavity in a centrifugal compressor [16]. The results indicated that the impeller backside cavity has an important effect on the efficiency, shaft power, and pressure ratio of the centrifugal compressor.…”
Section: Introductionmentioning
confidence: 99%
“…The CAES system is considered one of the energy storage technologies with the most development potential. The compressor is one of the most important components of the compressed air energy storage system, and its performance directly determines the efficiency and economy of the energy storage system [4,5]. The radial inlet chamber (RIC) is one of the important static components in the compressor unit.…”
Section: Introductionmentioning
confidence: 99%